Deep Vein Thrombosis in a Patient With an Absent Infrarenal IVC - Ayan Purkayastha; Kathryn Decarli; Mohit Bansal (Annals of Internal Medicine: Clinical Cases)
Absence of an infrarenal inferior vena cava is a rare anomaly that can be associated with deep venous thrombosis in young patients with no other provoking factors. Here, we present a patient case of a young man having groin pain and found to have gonadal vein and pampiniform plexus thromboses with an absent infrarenal inferior vena cava.